Development of Learning Media for Formalin Test Teaching Aids To Increase Interest in Learning and Chemical Literacy of Smk Students - Istiqomah Istiqomah; Anna Permanasari; Indarini Dwi Pursitasari (Universitas Pakuan, 2021)
This study aims to produce formalin test props as a learning aid to increase student interest in learning and chemical literacy of SMK students. The Research and Development method used in this study was a Four D (4D) design. The results of the development were examined for effectiveness through research involving 30 students majoring in Multi-media at Amaliah Vocational School. Testing the effectiveness of teaching aids in supporting the achievement of interest in learning and chemical literacy was carried out using the pre- experimental method. The teaching aids were validated by three lecturers consisting of expert lecturers. The instruments used include teaching aids validation instruments, learning observation formats, student response questionnaires, and chemical literacy test questions. The results of the development show that the teaching aids have met the requirements in terms of relevance, pedagogic, technical, originality and aesthetics. Furthermore, it was found that the use of teaching aids in learning could increase students' interest in learning and chemical literacy on average in the high category.